Determination of Natural and Synthetic Antioxidants in Palm Oil Using Fourier Transform Infrared Spectroscopy - Ammawath, Wanna (2006)
Lipid oxidation is one of the major deteriorative reactions in cooking oils and often results in a significant loss of quality. Various natural and synthetic antioxidants are used in the prevention or retardation of lipid oxidation. Routine quality control of antioxidants in oil turns out to be more and more important due to the increased environmental concern on the use of large volumes of solvents for analysis. Simple, accurate and rapid methods for determination of antioxidants in oils and fats industry are necessary to be developed. Fourier transform infrared (FTIR) spectroscopy has come of age in terms of price, performance and ease of use on determination of some natural and synthetic antioxidants.FTIR spectroscopy was developed in conjunction with partial least squares (PLS) technique for determining of -tocopherol in refined bleached and deodorized (RBD) palm olein. The calibration and validation samples were prepared by spiking known amounts of -tocopherol to produce a wide range of -tocopherol up to 2000 ppm. The accuracy of the method was comparable to that of the International Union of Pure and Applied Chemistry (IUPAC, 1992) method, with coefficients of determination (R2) from calibration samples of 0.9922 and standard error of calibration (SEC) of 53.54 at the FTIR spectral region 3100-2750 cm-1. For determination of -carotene in RBD palm olein using PLS calibration models coupled with FTIR spectral region at 980-915 cm-1, fifty RBD palm olein samples spiked with a known amount of standard (95%) -carotene to produce a wide range of concentrations up to 2000 ppm. The accuracy of the method was comparable to that of the PORIM method with R2 of 0.9950 and SEC of 19.47. FTIR spectra of RBD palm olein samples between 3600 and 2800 cm-1 were used for quantitative determination of tert-butylhydroquinone (TBHQ). Fifty stripped oil samples spiked with known amounts of TBHQ up to 300 mg/kg (ppm), were separated into two sets that of the calibration and validation models based on PLS analyses. The accuracy of the method was comparable to that of IUPAC method with R2 of 0.9961 and SEC 5.06. In the determination of butylated hydroxytoluene (BHT) content in RBD palm olein and RBD palm oil using FTIR spectroscopy, the accuracy of the method in both oils were comparable to that of the IUPAC method with an R2 of 0.9907 and SEC 8.47 for RBD palm olein, while an R2 of 0.9848 and SEC 10.73 was obtained for RBD palm oil. For determining butylated hydroxyanisole (BHA) of RBD palm oil and RBD palm olein, PLS coupled with the ‘leave-one-out” cross-validation procedure was used to verify the calibration model. FTIR spectral regions 3486-3170 and 1960-719 cm-1 gave an R2 of 0.9939 in RBD palm olein and an R2 of 0.9884 in RBD palm oil samples. Also, FTIR spectroscopy coupled with the PLS and PCR techniques was employed to construct the calibration models for determining propyl gallate (PG) in RBD palm olein. The results indicated that FTIR was a useful analytical tool for simple and rapid quantitative determination of PG in RBD palm olein in the spectral region 3707- 3262 cm-1. New FTIR methods developed for determining some synthetic and natural antioxidant used in palm oil product were found to be useful analytical tools, which were shown to significantly improved analysis time and avoided solvent-disposal problems. The results were found to be in good correlation and of comparable accuracy to PORIM and IUPAC methods. FTIR spectroscopy is advantageous as it is simple, rapid, accurate and requires minimum solvent as only acetone was used for cleaning NaCl windows. The method is suitable for routine quality control analysis with results obtainable in about 2 min.